Value of serology in predicting Pseudomonas aeruginosa infection in young children with cystic fibrosis. Issue 11 (1st October 2010) - Douglas, Tonia A; Brennan, Siobhain; Berry, Luke; Winfield, Kaye; Wainwright, Claire E; Grimwood, Keith; Stick, Stephen M; Sly, Peter D; ,
Abstract : Background: Early detection of Pseudomonas aeruginosa is essential for successful eradication. The accuracy of serum antibodies against specific and multiple P aeruginosa antigens at predicting lower airway infection in young children with cystic fibrosis (CF) was investigated. Methods: A commercial P aeruginosa multiple antigen (MAg) ELISA and an in-house exotoxin A (ExoA) ELISA were compared in two populations: a discovery population of 76 children (0.1–7.1 years) undergoing annual bronchoalveolar lavage (BAL)-based microbiological surveillance and a test population of 55 children (0.1–5.6 years) participating in the Australasian CF Bronchoalveolar Lavage Trial. Results: In the discovery population, P aeruginosa was cultured from BAL fluid (≥10 5 colony-forming units (cfu)/ml) in 15/76 (19.7%) children (median age 1.88 years). Positive MAg and ExoA serological results were found in 38 (50.0%) and 30 (39.5%) children, respectively. Positive (PPV) and negative (NPV) predictive values for serology at diagnosing P aeruginosa infection (≥10 5 cfu/ml) were 0.14 and 0.99 respectively (MAg assay) and 0.11 and 0.98 (ExoA assay). In the test population, P aeruginosa was cultured from BAL fluid (≥10 5 cfu/ml) in 16/55 (29.1%) children (median age 1.86 years) and from oropharyngeal swabs in 32/36 (88.9%). Positive MAg and ExoA serology was detected in 19 (34.5%) and 33 (60.0%) children, respectively. The PPV and NPV of serology were 0.26 and 0.94 respectively (MAg assay) and 0.19 and 0.98 (ExoA assay) and were marginally higher for oropharyngeal cultures. Conclusions: Measuring serum antibody responses against P aeruginosa is of limited value for detecting early P aeruginosa infection in young children with CF.